2018
DOI: 10.1016/j.rmed.2018.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary function in former very low birth weight preterm infants in the first year of life

Abstract: Preterms had a high prevalence of abnormal pulmonary function and lower pulmonary function in comparison to term infants. Prematurity, intrauterine growth restriction, respiratory support and recurrent wheezing were associated with abnormal pulmonary function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 29 publications
5
14
1
2
Order By: Relevance
“…This diversity arises from the complex interaction of structures damaged by oxygen and mechanical ventilation injury in the premature lung and a developmental healing process . However, the main pulmonary features of BPD might be an obstructive lung pattern, as shown in other studies . Since the severity of BPD could be largely related to the degree of airway obstruction, t PEF / t E was found to be a useful airflow limitation marker to assess the severity of the decrease in pulmonary function in BPD, as shown in our study.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This diversity arises from the complex interaction of structures damaged by oxygen and mechanical ventilation injury in the premature lung and a developmental healing process . However, the main pulmonary features of BPD might be an obstructive lung pattern, as shown in other studies . Since the severity of BPD could be largely related to the degree of airway obstruction, t PEF / t E was found to be a useful airflow limitation marker to assess the severity of the decrease in pulmonary function in BPD, as shown in our study.…”
Section: Discussionsupporting
confidence: 79%
“…1 However, the main pulmonary features of BPD might be an obstructive lung pattern, as shown in other studies. [30][31][32][33][34] Since the severity of BPD could be largely related to the degree of airway obstruction, t PEF /t E was found to be a useful airflow limitation marker to assess the severity of the decrease in pulmonary function in BPD, as shown in our study.…”
Section: Discussionsupporting
confidence: 64%
“…This might have biased our results because prenatal tobacco exposure was not considered in our analysis. Nevertheless, only 3% of mothers of our study cohort reported smoking during pregnancy, and our previous study did not reveal any effect of maternal smoking on lung function 13,14 .…”
Section: Mocontrasting
confidence: 64%
“…To compare the lung function indexes of preterm and term healthy infants, data of the control population from our previous studies were included in the analysis 13,14 . In infants with no BPD, although poor performance was initially observed in some indexes of lung function (Vt, Crs, V'max FRC , FEV 0.5 , and FEF ), these indexes had eventually normalized later in life (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Very low birth weight (<1500 g) has been associated with poor lung function at 6-12 months of corrected age [65]. Birth weight is associated with lung function in term-born children at 8-9 years, but less so at 14-17 years.…”
Section: Low Birth Weightmentioning
confidence: 99%